Transforming Growth Factor β (TGF-β)Inhibits Expression of Fibrinogen and Factor VII in a Hepatoma Cell Line - Hassan, Jane H; Chelucci, Cristiana; Peschle, Cesare; Sorrentino, Vincenzo (Thrombosis and Haemostasis, 1992)
We have investigated the effect(s) of transforming growth factor (TGF)-β1 and interleukin (IL)-6 on the expression of fibrinogen and blood coagulation factors VII, IX, X mRNAs in a hepatoma cell line (Hep 3B). The results indicate that TGF-β induces a decrease of the basal level of fibrinogen and factor VII mRNAs, but does not affect factor X expression. Furthermore, TGF-β efficiently antagonizes the IL-6 induction of fibrinogen mRNA at late (12-48 h) but not early (6 h) times: this effect is apparently mediated by posttranscriptional mechanism(s). These findings, together with previously reported data on the inhibitory effect of TGF-β on acute phase genes (e.g., ApoAl and albumin), suggest a role for TGF-β in the regulation of liver genes expression. The early stimulatory and late inhibitory effect exerted by IL-6 and TGF-β respectively on fibrinogen mRNA level may play a role in the regulatory mechanism(s) of clot formation in a variety of conditions.